The effect of a mesenteric traction syndrome on internal carotid artery blood flow - Olesen, Niels D.; Egesborg, Astrid H.; Frederiksen, Hans-Jørgen; Svendsen, Lars B.; Secher, Niels H. (Frontiers in Anesthesiology, 2023)
Purpose During abdominal surgery, manipulation of internal organs may induce a “mesenteric traction syndrome” (MTS) including a triad of flushing, hypotension, and tachycardia that lasts for approximately 30 min. We evaluated whether MTS affects internal carotid artery blood flow. Methods This prospective cohort study included 27 patients aged 65 ± 11 years (mean ± SD) undergoing stomach resection (n = 12), esophageal resection (n = 14), or gastro-entero anastomosis (n = 1) during propofol-remifentanil and thoracic epidural anesthesia. Duplex ultrasound determined internal carotid artery blood flow, laser Doppler flowmetry assessed forehead skin blood flow, and near-infrared spectroscopy determined cerebral oxygenation. Development of MTS was defined by flushing within 60 min after incision. Results Seven patients developed MTS 22 [20–26; median (IQR)] min after incision and at that time the change in heart rate (to 87 ± 13 vs. 70 ± 11 bpm; P = 0.0007) and skin blood flow (to 214 (134–269) vs. 84 (59-112 PU; P = 0.0044) was higher in the patients who developed MTS as compared to those who did not, while mean arterial pressure (63 ± 13 vs. 64 ± 14 mmHg; P = 0.1433), cerebral oxygenation (69 ± 9% vs. 63 ± 10%; P = 0.2485), and internal carotid artery flow (225 ± 53 vs. 203 ± 69 ml/min; P = 0.9529) were similar. Conclusion Hemodynamic perturbations are observed in some patients in response to manipulation of the viscera, but the development of MTS appears not to influence internal carotid artery flow. Clinical trial registration https://clinicaltrials.gov/ct2/show/NCT02951273?term=NCT02951273&rank=1, identifier: NCT02951273.